A Comprehensive Characterization of Different Fractions of Corn Stover and Their Relationships to Multipollutant Sorption Characteristics. (6th August 2021) - Peng, Dan; Ouyang, Fan; Deng, Min; Nie, Lei; Kong, Sifang
Abstract : Corn stover (CS) is mainly composed of three parts: pith (CSP), rind (CSR), and leaf (CSL). These parts have different lignocellulosic constituents and structural properties. Herein, biosorbents derived from individual corn stover constituents were prepared in an effort to determine the significance of each constituent for multipollutant removal. In this study, SEM, BET, XRD, FTIR, XPS, fibre composition, and contact angle measurements were used to characterize and analyse the physical and chemical properties of the three components of CS and to study their adsorption effects, adsorption isotherms, and kinetics. The lignocellulosic compositions of CSP and CSR were similar, the cellulose content in CSP and CSR was significantly higher than that in CSL, and the hemicellulose content of CSL was much higher than those of CSP and CSR. The minimum lignin content was found in CSP, and the maximum lignin content was found in CSR. The results show that each component had a certain adsorption effect on typical organic pollutants (antibiotics, oils, and dyes). CSP had the strongest oil adsorption capacity, CSR was more suitable for adsorbing antibiotics, and CSL had outstanding adsorption capacity for dye. The pseudo-second-order model and the Langmuir adsorption isotherm model could describe the adsorption processes well, and they consisted of monolayer adsorption accompanied by chemical adsorption reactions. The focus of this study was to provide references for selecting effective adsorbent precursors to remove organic pollutants from wastewater.